Route Duration Modeling For Mobile Ad-Hoc Networks - VEENA B K (2008)
INTERNAL GUIDE : Rajapuspha . EXTERNAL GUIDE : Harshad Patil USN No : 1MJ07SCS18 CARRIED OUT AT : Planet -I Technologies Bangalore-560 054 ACC NO : PC68
Keywords: M. Tech Computer Science